Investigation of geometric effects on fluid viscosity using the falling ball method - Akhyan, Amnur; Ma’a, Mustaza; Irdam, Fortinov Akbar; Alvarez, Alvin; Nugraha, Nurcahya; Nurkhamdi, Nurkhamdi (Politeknik Negeri Lhokseumawe, 2025)
The falling ball method, based on Stokes law, is a simple yet accurate technique for determining fluid viscosity, though its precision is influenced by factors such as wall, Reynolds, end, memory, and off-center effects. This study aims to determine the effect of spherical geometry on the fluid viscosity value represented by the sphericity factor . An experimental study was conducted to examine its accuracy of viscosity values to produce the correction factor. The sphericity factors studied were 0.993, 0.976, and 0.949. To reduce the uncertainty caused by the wall effect, the ratio db/Dt was 0.071, using a 5.8mm diameter plastic ball and SAE 40 oil fluid at 32.4°C. Terminal velocity (??) was obtained by analyzing the video of the ball falling in the fluid, which was displayed on the tracker software. The video was taken using a 1080p, 60 fps camera. Wall and Reynolds effect correction factors were used to amend experimental viscosity values. The result indicates the viscosity will be accurately determined by selecting a larger sphericity value of the ball during the experimental process. It will reduce the necessity of correction factors to obtain the value of fluid viscosity.